Rozwiązane

Wykonaj mnozenie i zredukuj wyrazy podobne :
a) ( x - 1 ) ( x ³ + x ² + x + 1 )
b) ( x + 1 ) ( x ³ - x ² + x - 1 )



Odpowiedź :

Beetle
a) ( x - 1 ) ( x ³ + x ² + x + 1 )=
=xdo4 + x³ + x ² +x - x³ - x² - x -1=
=x (do 4) -1
b) ( x + 1 ) ( x ³ - x ² + x - 1 ) =
= x (do 4) - x³ + x² - x + x³ - x² +x -1=
= x (do 4) - 1
a) ( x - 1 ) ( x ³ + x ² + x + 1 ) = x(do czwartej) + x³ + x² +x - x³ - x² - x - 1 =
= x(do czwartej) - 1
b) ( x + 1 ) ( x ³ - x ² + x - 1 ) = x (do czwartej) - x³ + x² - x + x³ - x² + x - 1 =
= x (do czwartej) -1
a) x^4+x^3+x^2+x-x^3-x^2-x-1=x^4-1
b)x^4-x^3+x^2-x+x^3-x^2+x-1=x^4-1